A High‐Capacitance Salt‐Free Dielectric for Self‐Healable, Printable, and Flexible Organic Field Effect Transistors and Chemical Sensor. (12th May 2015) - Huang, Weiguo; Besar, Kalpana; Zhang, Yong; Yang, Shyuan; Wiedman, Gregory; Liu, Yu; Guo, Wenmin; Song, Jian; Hemker, Kevin; Hristova, Kalina; Kymissis, Ionnis J.; Katz, Howard E.
<x xml:space="preserve">Abstract</x> Printable and flexible electronics attract sustained attention for their low cost, easy scale up, and potential application in wearable and implantable sensors. However, they are susceptible to scratching, rupture, or other damage from bending or stretching due to their "soft" nature compared to their rigid counterparts (Si‐based electronics), leading to loss of functionality. Self‐healing capability is highly desirable for these "soft" electronic devices. Here, a versatile self‐healing polymer blend dielectric is developed with no added salts and it is integrated into organic field transistors (OFETs) as a gate insulator material. This polymer blend exhibits an unusually high thin film capacitance (1400 nF cm−2 at 120 nm thickness and 20–100 Hz). Furthermore, it shows pronounced electrical and mechanical self‐healing behavior, can serve as the gate dielectric for organic semiconductors, and can even induce healing of the conductivity of a layer coated above it together with the process of healing itself. Based on these attractive properties, we developed a self‐healable, low‐voltage operable, printed, and flexible OFET for the first time, showing promise for vapor sensing as well as conventional OFET applications.